2021
DOI: 10.1101/2021.10.23.465561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Biodegradable, Tacrolimus-releasing Nerve Wrap Promotes Peripheral Nerve Regeneration

Abstract: Axonal regeneration following nerve repair is slow and often incomplete, resulting in poor functional recovery and sometimes lifelong disability. Yet, there are no FDA-approved therapies available to promote nerve regeneration. Tacrolimus accelerates axonal regeneration, but systemic side-effects presently outweigh its potential benefits for peripheral nerve surgery. We have developed a biodegradable drug delivery system for the sustained local release of tacrolimus at the nerve repair site, with suitable prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…2 A). 52 Tacrolimus was encapsulated in the core of each fiber to create a sustained-release profile. Detailed physical characterization, drug release kinetics, and bioactivity studies for this biodegradable nanofiber DDS have been reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2 A). 52 Tacrolimus was encapsulated in the core of each fiber to create a sustained-release profile. Detailed physical characterization, drug release kinetics, and bioactivity studies for this biodegradable nanofiber DDS have been reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed physical characterization, drug release kinetics, and bioactivity studies for this biodegradable nanofiber DDS have been reported previously. 52 Briefly, the electrospun matrices were sectioned in 0.5 × 2.5-mm sheets, yielding 223 ± 65 µg tacrolimus each. The DDSs were subsequently irradiation sterilized (25 Gy) and stored at 4°C until use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations